The Source Provenance of an Obsidian Eden Point from Sierra County, New Mexico. (2nd January 2016) - Dolan, Sean G.; Berryman, Judy; Shackley, M. Steven
Abstract : Eden projectile points associated with the Cody complex are underrepresented in the late Paleoindian record of the American Southwest. EDXRF analysis of an obsidian Eden point from a site in Sierra County, New Mexico demonstrates this artifact is from the Cerro del Medio (Valles Rhyolite) source in the Jemez Mountains. We contextualize our results by examining variability in obsidian procurement practices beyond the Cody heartland in southcentral New Mexico.